North Africa in the Tourist Guidebooks of the 19th and Early 20th Centuries - Manai, Adel (Mediterranean Journal of Social Sciences, 2020)
By the dawn of the twentieth century, a guidebook was a vital element of a tourist’s packing list and an item, which a tourist could not do without. The guidebook not only provided practical and useful information, but also advised the tourist about what ‘ought to be seen’. It accompanied the development and maturation of modern tourism and witnessed an explosion in the second half of the 19th century and after. The guidebook was gradually improved, highly commercialized, popularized, and extended to many parts of the world and somehow managed to impose ‘beaten tracks’ on tourists. Similarly, the guidebook accompanied European colonial schemes, served as a tool for them and reflected their agendas and the mindset of the age. This paper is based on a large number of French and English guidebooks spanning approximately the period between the mid-nineteenth and early twentieth centuries and addresses the following questions: when and how was North Africa included in the tourist guidebook literature? What visions did the guidebook provide of the region? How far did the guidebooks contribute to placing North Africa in the global tourist networks and with what effect?